2010
DOI: 10.1353/csd.2010.0010
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence of the Reliability and Validity of a Quantitative Measure of Self-Authorship

Abstract: This article presents preliminary evidence of the reliability and validity of a measure of self-authorship derived from 18 items in the Career Decision Making Survey. The research conceptualizes a quantitative measure of self-authorship as a three-part score that reflects level of agreement with statements at each of the first three phases of development toward self-authorship. The instrument could be used to assess the outcomes of initiatives designed to promote growth in the development of self-authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(104 citation statements)
references
References 23 publications
2
99
3
Order By: Relevance
“…Elizabeth Creamer and Anne Laughlin (2005) and Laughlin and Creamer (2007) found that their self-authorship questionnaire provided information about whom students consulted for career decisions rather than how they constructed their consultations, the latter information emerging in interviews. Aware of the assessment challenges recounted here and in the interest of providing a psychometrically sound measure for assessing educational practice to promote self-authorship, Creamer continued work on the Career Decision Making Survey, which includes Likert-type items keyed to External Formulas, Crossroads, and early Self-Authoring (Creamer, Baxter Magolda, and Yue, 2010). Using the survey with college juniors and seniors resulted in eighteen items that show promise for assessing the three developmental dimensions, the three early developmental phases, and a matrix summary that portrays a range of meaning making (Creamer, Baxter Magolda, and Yue, 2010).…”
Section: Assessment Formatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elizabeth Creamer and Anne Laughlin (2005) and Laughlin and Creamer (2007) found that their self-authorship questionnaire provided information about whom students consulted for career decisions rather than how they constructed their consultations, the latter information emerging in interviews. Aware of the assessment challenges recounted here and in the interest of providing a psychometrically sound measure for assessing educational practice to promote self-authorship, Creamer continued work on the Career Decision Making Survey, which includes Likert-type items keyed to External Formulas, Crossroads, and early Self-Authoring (Creamer, Baxter Magolda, and Yue, 2010). Using the survey with college juniors and seniors resulted in eighteen items that show promise for assessing the three developmental dimensions, the three early developmental phases, and a matrix summary that portrays a range of meaning making (Creamer, Baxter Magolda, and Yue, 2010).…”
Section: Assessment Formatsmentioning
confidence: 99%
“…Aware of the assessment challenges recounted here and in the interest of providing a psychometrically sound measure for assessing educational practice to promote self-authorship, Creamer continued work on the Career Decision Making Survey, which includes Likert-type items keyed to External Formulas, Crossroads, and early Self-Authoring (Creamer, Baxter Magolda, and Yue, 2010). Using the survey with college juniors and seniors resulted in eighteen items that show promise for assessing the three developmental dimensions, the three early developmental phases, and a matrix summary that portrays a range of meaning making (Creamer, Baxter Magolda, and Yue, 2010). Additional efforts to develop paper-and-pencil measures of self-authorship have been inconclusive to date (Goodman and Seifert, 2009;Pizzolato and Chaudhari, 2009).…”
Section: Assessment Formatsmentioning
confidence: 99%
“…In effort to explain this challenge, one must first understand the difference between the structure and content of a thought. The content of an individual's thought refers to what he or she thinks, while the structure refers to the reason or justification for thinking it (Creamer et al, 2010). For example, two individuals may share in their thought that marijuana should be legalized.…”
Section: Challengesmentioning
confidence: 99%
“…Researchers developed a new measure for self-authorship (Creamer et al, 2010) referred to as the Career Decision Making Survey-Self Authorship (CDMS-SA). The CDMS-SA will be explained and analyzed in detail throughout the following section, as it is the instrument employed in this study.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation